Global Warming: Causes, Impacts, and Mitigation Strategies - Brian Chad (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Global warming is a pervasive environmental crisis that has garnered worldwide attention due to its profound and far-reaching implications. This comprehensive review article aims to provide a thorough examination of the multifaceted aspects of global warming, including its causes, impacts, and mitigation strategies. Drawing upon a wealth of scientific research and empirical data, this study offers a comprehensive synthesis of the current state of knowledge on this critical issue. The core of this review centers on the multifaceted impacts of global warming across various sectors. It highlights the increasingly frequent and severe heatwaves, melting ice caps and glaciers, rising sea levels, and disruptions to ecosystems. Furthermore, it delves into the socio-economic consequences, including threats to food security, displacement of populations, and potential conflicts arising from resource scarcity.